Human digestive physiology and evolutionary diet: a metabolomic perspective on carnivorous and scavenger adaptations - Clemente-Suárez, Vicente Javier (2025)
This review examines human digestive physiology and metabolic adaptations in the context of evolutionary dietary patterns, particularly those emphasizing carnivorous and scavenging behaviors. By integrating metabolomic data with archaeological, anatomical, and microbiological evidence, the study explores how early hominins adapted to intermittent but energy-dense animal-based diets. The analysis highlights the development of hepatic insulin resistance, enhanced fat and protein metabolism, and shifts in gut microbiota diversity as physiological signatures of meat consumption. Comparative evaluations of digestive enzyme profiles, intestinal morphology, and salivary composition underscore humans’ omnivorous flexibility and partial carnivorous specialization. Additionally, biomarkers such as ketone bodies, branched-chain amino acids, and trimethylamine-N-oxide are identified as metabolic indicators of habitual meat intake. These adaptations, though once evolutionarily advantageous, are discussed in relation to current metabolic disorders in modern nutritional contexts. Overall, this review presents a metabolomic framework for understanding the evolutionary trajectory of human digestion and its implications for health and dietary recommendations.